The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8036804
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional ephaptic stimulation between two myelinated axons

Abstract: Providing realistic sensory feedback for prosthetic devices strongly relies on an accurate modelling of machine-nerve interfaces. Models of these interfaces in the peripheral nervous system usually neglect the effects that ephaptic coupling can have on the selectivity of stimulating electrodes. In this contribution, we study the ephaptic stimulation between myelinated axons and show its relation with the separation between fibers and the conductivity of the medium that surrounds them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It is not clear whether the observed change in CAP velocity agrees with modelling predictions in [24][25][26][27], that ephaptic interactions slow down the CAP, because the models did not consider external current. In the present study, it is conceivable that the partially excited membranes took less time to depolarize, which would produce the observed increase in CAP velocity.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is not clear whether the observed change in CAP velocity agrees with modelling predictions in [24][25][26][27], that ephaptic interactions slow down the CAP, because the models did not consider external current. In the present study, it is conceivable that the partially excited membranes took less time to depolarize, which would produce the observed increase in CAP velocity.…”
Section: Discussionmentioning
confidence: 82%
“…These interactions can improve synchrony of activity within populations of neural cells or triggering of neural activity in subthreshold cells, and may be induced either by naturally occurring physiological effects [17][18][19] or by artificially increasing excitability using chemicals [20,21] and subthreshold electrical current [18,22,23]. In myelinated nerve fibres, modelling studies predict ephaptic interactions alter the propagation velocities of action potentials in neighboring active fibres which improves synchrony [24][25][26][27], and an in vivo study on rat showed increased activity in response to an electrical stimulus when it was temporally coupled with a compound action potential (CAP) [28]. Increasing synchrony and localized triggering of new action potentials in peripheral nerves using a subthreshold current presents an exciting prospect because such a paradigm could improve the signal to noise ratio in peripheral nerve interfaces, aid physical rehabilitation after spinal cord injury and stroke, and provide insight into mechanisms of subthreshold current neuromodulation therapies.…”
Section: Introductionmentioning
confidence: 99%